O Brasil “civilizado” e o Japão “bizarro” na revista Kosmos: imagens contrastantes - Okamoto, Mônica Setuyo [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
Este artigo discute as relações entre idéias de progresso da capital federal brasileira no começo do século XX e a imagem bizarra do Japão e dos japoneses veiculadas dentro de um dos periódicos brasileiros mais requintados da época: a revista Kosmos. Em contraposição aos artigos de louvor às melhorias urbanas promovidas pelo governo carioca; as crônicas de viagem de países “exóticos” como o Extremo Oriente tiveram um papel fundamental na promoção da auto-estima da elite brasileira que se pretendia civilizada, moderna e branca.

This article discusses the relation between ideas of progress of the federal capital of Brazil in the early twentieth century and the bizarre image broadcast on Japan and Japanese in one of the finest Brazilian journals of the time: the Kosmos journal. In contrast to the articles of praise to urban improvements undertaken by the government of Rio de Janeiro, chronicles the journey of exotic countries as the Far East played a key role in promoting self-esteem of the Brazilian elite that was intended civilized, modern and white.
Brazil “civilized” and Japan “bizarre” in the journal Kosmos: contrasting images
Keywords: Japan; Brazil and journal Kosmos; Japão; Brasil e revista Kosmos